Examining the mediating role of work engagement in the relationship between corporate social responsibility and turnover intention: Evidence from nigeria - Olubanke Tolulope Bayode; Ana Patrícia Duarte (Administrative Sciences, 2022)
The subject of corporate social responsibility (CSR) has drawn the attention of many scholars and practitioners in the administrative sciences field. However, few studies have been carried out on Nigerian employees' perspectives on CSR and on how CSR affects their attitudes and behaviors at work. The present study sought to contribute to narrowing this gap by examining how CSR perceptions, work engagement, and turnover intention are related in a sample of Nigerian workers. More specifically, this study had triple aims: first, describe employees' perceptions of their employers' involvement in different CSR domains; second, examine how CSR perceptions were related to employees' levels of work engagement and turnover intention; third, analyze work engagement intervention as a mediator in the relationship between CSR perceptions and turnover intention. The sample included 118 employees from different organizations who voluntarily participated in an online survey. The findings revealed that respondents consider that their employer organizations have relatively high involvement in CSR activities, especially activities towards customers, employees, and stockholders. Findings also revealed that employees' perceptions of CSR are related to diminishing levels of turnover intention, via increased work engagement. Therefore, organizations can invest in CSR activities to foster positive employee outcomes in Nigeria.
Keywords: 350; corporate social responsibility; Nigeria; turnover intention; work engagement